2020
DOI: 10.1111/vde.12901
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive herpesvirus‐associated erythema multiforme in a cat

Abstract: Erythema multiforme (EM), an uncommon immune-mediated skin disorder of cats, conceivably could be triggered by feline herpesvirus type-1 (FHV-1) infection, in a manner analogous to human herpesvirus-associated EM (HAEM). This report describes a 10-year-old Persian-mixed cat with a presumptive diagnosis of HAEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…1 Biopsy samples from all of the ferrets in this study demonstrated the histological criteria of EM including lymphocytic exocytosis and satellitosis, multilevel keratinocyte apoptosis and interface dermatitis. [1][2][3][4][5][6][7]9,10 Apoptotic keratinocytes also were frequently present within the follicular epithelium. The interface dermatitis was classified as cell-poor lymphocytic to lymphoplasmacytic, with lesser neutrophilic infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 Biopsy samples from all of the ferrets in this study demonstrated the histological criteria of EM including lymphocytic exocytosis and satellitosis, multilevel keratinocyte apoptosis and interface dermatitis. [1][2][3][4][5][6][7]9,10 Apoptotic keratinocytes also were frequently present within the follicular epithelium. The interface dermatitis was classified as cell-poor lymphocytic to lymphoplasmacytic, with lesser neutrophilic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…canine parvovirus and feline herpesvirus). 9,10 The most frequently reported precipitating factor is a drug hypersensitivity reaction. [1][2][3][4][5][6][7] Drug-induced EM has been seen with sulfonamides, penicillins and cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations